2015
DOI: 10.1002/ece3.1819
|View full text |Cite
|
Sign up to set email alerts
|

Drought and shade deplete nonstructural carbohydrate reserves in seedlings of five temperate tree species

Abstract: Plants that store nonstructural carbohydrates (NSC) may rely on carbon reserves to survive carbon‐limiting stress, assuming that reserves can be mobilized. We asked whether carbon reserves decrease in resource stressed seedlings, and if NSC allocation is related to species' relative stress tolerances. We tested the effects of stress (shade, drought, and defoliation) on NSC in seedlings of five temperate tree species (Acer rubrum Marsh., Betula papyrifera Marsh., Fraxinus americana L ., Quercus rubra L., an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
41
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 49 publications
(96 reference statements)
10
41
4
Order By: Relevance
“…This is interesting given that nectar is predominantly composed of water and sugar, both of which are likely limited in dry conditions. Furthermore, photosynthetic carbon assimilation can drop due to stomatal closure (Lawlor and Cornic, ) and decrease the availability of nonstructural carbohydrates such as sucrose (Maguire and Kobe, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting given that nectar is predominantly composed of water and sugar, both of which are likely limited in dry conditions. Furthermore, photosynthetic carbon assimilation can drop due to stomatal closure (Lawlor and Cornic, ) and decrease the availability of nonstructural carbohydrates such as sucrose (Maguire and Kobe, ).…”
Section: Discussionmentioning
confidence: 99%
“…Trees adapted to drier conditions may invest more in non-structural carbon reserves (Maguire and Kobe, 2015) to maintain growth under adverse conditions, but it may be more difficult for them to replenish these reserves and recover growth subsequently.…”
Section: Resistance and Resilience Of Radial Growth To Drought Decreamentioning
confidence: 99%
“…The depletion of nonstructural carbohydrate pools has been suggested to result from the extended closure of stomata during drought leading to reduced photosynthesis and eventually a shortage of carbohydrate metabolites in different tree tissues (Hartmann, ). However, tree carbohydrate reserve pools were often only measured towards the end of drought periods (Adams et al, ; Galiano, Martinez‐Vilalta, & Lloret, ) or observed in seedlings under additional shading treatment (Hartmann, McDowell, & Trumbore, ; Hartmann, Ziegler, & Trumbore, ; Hartmann, Ziegler, Kolle, & Trumbore, ; Maguire & Kobe, ). Hence, most of the information on the vulnerability of temperate trees to xylem embolism and carbohydrate depletion was obtained in experimental work or from very few scattered measurements throughout or at the end of a given period of time.…”
Section: Introductionmentioning
confidence: 99%